Entangled Interactions between Religions and National Identities in the Eastern Borderland of Europe - Aoshima, Yoko (Lithuanian Studies Without Borders Ser., 2020)
Thisbook elucidates the complicated relationship between religion and nationalconsciousness in the modern world, shedding light on various cases in Centraland Eastern Europe. Though those analyses, the authors show how religion, far fromdisappearing, strongly impacted on the emerging national consciousness.